(untitled) (Bangladesh Journal of Medicine, 2024)
Ensuring the well-being of the population through the provision of adequate health services is a fundamental human right. Despite the progress made in Bangladesh’s health sector, there are still challenges that require attention. These challenges include the need for comprehensive health policies and effective program implementation. With the current state of the public health system, it is crucial to address factors such as inadequate health infrastructure, high poverty rates, rapid population growth, and insufficient budget allocation for the health sector. Furthermore, addressing the scarcity of essential medical supplies and equipment, as well as improving administrative management, will significantly impact the health service system positively. By prioritizing these issues, we can ensure that the people of Bangladesh have access to quality health services. Bangladesh J Medicine, 2024; Vol. 35, No. 2, Supplementation: 130